Art and Shamanisms between Global North and Global South: tensions, knowledge, and artistic practices in the works of Joseph Beuys, Claudia Andujar, and Bené Fonteles - Palma, Adriana Amosso Dolci Leme (2025)
This research examines the relationships established between art and shamanism through comparative analyses of works and actions developed by some artists who connected, using distinct strategies, with varied conceptions of shamanism and/or the figure of the shaman, especially during the second half of the twentieth century. The study focuses on three artists whose careers demonstrate, each in their own way, engagement with different conceptions of shamanisms: Bené Fonteles (1955) and Claudia Andujar (1931), both active in Brazil since the 1970s, and the German Joseph Beuys (1921-1986), whose work in the European art scene was widely disseminated internationally, including appearances in the Brazilian art circuit during that period. The reflections conceived by these artists evolved into activities that extended beyond the artistic sphere, spilling over into pedagogical, political, social, and ecological practices. Thus, the theoretical and conceptual notions each artist held regarding education, politics, ecology, and society are delineated, analyzed, and problematized. The research seeks to correlate the life and production contexts of these artists as a means of exploring similarities, differences, and relationships between the epistemologies developed in the Global North and the Global South, drawing on contexts from Brazil and Germany